The composition of bacteria in gut and beebread of stingless bees (Apidae: Meliponini) from tropics Yunnan, China - Tang, Qi-He; Miao, Chun-Hui; Chen, Yi-Fei; Dong, Zhi-Xiang; Cao, Zhe; Liao, Shi-Qun; Wang, Jia-Xuan; Wang, Zheng-Wei; Guo, Jun (Antonie van Leeuwenhoek, 2021)
Stingless bees are the main pollinators in tropical and subtropical regions. However, there are only a few studies on the structure and composition of bacteria in the gut and beebread of stingless bees, especially in China. To address this shortage of information, we characterized the microbiota of three common species of stingless bees ( Lepidotrigona terminata , Lepidotrigona ventralis and Tetragonula pagdeni ) and beebread samples of T. pagdeni . The results showed that the gut of stingless bees contained a set of dominant bacteria, including Acetobacter -like, Snodgrassella , Lactobacillus , Psychrobacter , Pseudomonas , Bifidobacterium and other species. The gut microbiota structures of the three stingless bees were different, and the abundances of bacterial species in the gut varied between communities of the same bee species. The reasons for this are manifold and may include food preference, age and genetic differences. In addition, the abundances of Lactobacillus, Carnimonas , Escherichia-Shigella, Acinetobacter and other species were high in the beebread of stingless bees. In conclusion, our findings reveal the bacteria composition and structure of the gut and beebread of stingless bees in China and deepen our understanding of the dominant bacteria of the gut and beebread of stingless bees.